Integrative analysis of the multi-omics reveals the stripe rust fungus resistance mechanism of the TaPAL in wheat - Liu, Rong; Lv, Xue; Wang, Xiaohua; Yang, Li; Cao, Jun; Dai, Ya; Wu, Wang; Wu, Yu (Frontiers in Plant Science, 2023)
Wheat is one of the major food crops in the world. However, stripe rust fungus significantly decreases wheat yield and quality. In the present study, transcriptomic and metabolite analyses were conducted in R88 (resistant line) and CY12 (susceptible cultivar) during Pst-CYR34 infection due to the limited availability of information regarding the underlying mechanisms governing wheat-pathogen interactions. The results revealed that Pst infection promoted the genes and metabolites involved in phenylpropanoid biosynthesis. The key enzyme gene TaPAL to regulate lignin and phenolic synthesis have a positive resistance contribution to Pst in wheat, which was verified by the VIGS technique. The distinctive resistance of R88 is regulated by the selective expression of genes involved in the fine-tuning of wheat-Pst interactions. Furthermore, metabolome analysis suggested that lignin biosynthesis-related metabolite accumulation was significantly affected by Pst. These results help to elucidate the regulatory networks of wheat-Pst interactions and pave the way for durable resistance breeding in wheat, which may ease environmental and food crises around the world.